Persepsi Generasi Z pada Konten Iklan Sampo Rejoice x Kiky Saputri versi “Rambut No Drama” - Chandra, Vanessa; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The increasing number of internet users in Indonesia is used by many companies or brands as an opportunity to market their products through advertisements on social media. One of them is Rejoice shampoo which creates promotional advertising content on YouTube social media. One of the active YouTube users is Generation Z, so it has the potential to be a subject in this study. The purpose of this research is to describe Generation Z perception of Rejoice shampoo creative advertising content on YouTube. Creative advertising content tends to attract the attention of potential consumers more than non-creative ones. The theoretical basis used in this study is marketing communications, advertising, creative advertising, advertising on social media, and perception. This research was conducted with a qualitative approach. Researchers also conducted in-depth interviews with four informants who met the criteria. The perception that appears in Generation Z is divided into three stages, namely sensation, attention, and interpretation. The results of this study indicate that Generation Z perception of the content of the Rejoice x Kiky Saputri shampoo advertisement version of